Digital Urban Network Connectivity: Global and Chinese Internet Patterns - Emmanouil Tranos; Karima Kourtit; Peter Nijkamp (Tinbergen Institute, 2012)
The majority of cities in our world is not only connected through conventional physical infrastructure, but increasingly through modern digital infrastructure. This paper aims to test whether digital connectivity leads to other linkage patterns among world cities than traditional infrastructure. Using a generalized spatial interaction model, this paper shows that geography (and distance) still matters for an extensive set of world cities analysed in the present study. With a view to the rapidly rising urbanization in many regions of our world, the attention is next focused on the emerging large cities in China in order to test the relevance of distance frictions - next to a broad set of other important explanatory variables - for digital connectivity in this country. Various interesting results are found regarding digital connectivity within the Chinese urban system, while also here geography appears to play an important role.
Keywords: O18; H54; P25; 330; Digital Networks; Internet; Connectivity; World Cities; Death of Distance; Centrality; Small-World Networks; Clustering; Gravity Model